Application of oxide nanoparticles obtained by proteic sol-gel and mechanical alloying in third generation solar cells - Pereira, Maurício de Sousa (2017)
The development of new energy technologies is crucial to climate stability and security in the planet. Considering the current energy consumption on a global scale it becomes evident the need to develop new alternative energy sources, especially those that are preferentially renewable, clean and economical. Among the renewable energy sources currently used, solar energy is an attractive source because it is abundant and free of CO2 . Photovoltaic solar cells are just one of several ways to harness solar energy, converting it directly into electricity. Currently, traditional solar technologies have been used to a limited degree in energy production because of the high costs. However, third generation solar cells offer a potential route for large-scale solar energy deployment because they utilize materials that are abundant in nature and low cost production technologies. Commonly called excitonic solar cells, third generation photovoltaic devices encompass a wide variety of solar cells such as dye-sensitized solar cells and organic solar cells. Both offer a technically and economically reliable alternative to the current concept of photovoltaic devices based on p-n junctions. In this doctoral thesis, nanoparticles of semiconductor oxides and spinel ferrites produced by protein sol-gel and mechanical alloying were applied to dye-sensitized and organic solar cells in order to improve their efficiency and stability. Prior to their application, the nanoparticles had their thermal, structural, optical and magnetic properties characterized. Solar cells efficiency was evaluated by electrical characterization methods such as current–voltage curves and external quantum efficiency measurements, and their stability, when applicable, was studied by accelerated and real outdoor degradation tests. Nanoparticles of semiconduncting SnO2 produced by the proteic sol-gel method were successfully applied as photoanodes in dye-sensitized solar cells. The results confirmed the formation of spherical nanoparticles of rutile SnO2 with an optical absorption band in the ultraviolet region near the visible light range. The performance of the cells was found to be in line with results in the literature. Moreover, nanoparticles of Fe-doped SnO2 diluted magnetic seminconductor and CoFe2O4 spinel ferrite produced by mechanical alloying and proteic sol-gel, respectively, were applied as dopants in the active layer of organic solar cells. An improvement on photovoltaic parameters that may lead to better cell efficiency and stability was observed for devices with doped active layers. The results are indications that the addition of magnetic oxide nanoparticles in the active layer of organic solar cells has the potential to contribute to the extension of lifetime and improvement of efficiency and stability of these devices.